Prediction of the cutting tool edge position and orientation accuracy through error synthesis of spindle elements - Teixeira C.R. (2005)
Achieving workpiece high accuracy at low cost is one of the greatest challenges in the machining industry. The runout of the cutting tool is prejudicial to precision machining, causing errors in the machined part, variation in the tool life, and premature tool breakage. This paper focuses on modelling the cutting tool edge position and orientation variations of a spindle system. This is a static approach based on the errors of the spindle elements. A kinematic model of the spindle/toolholder/cutting tool using homogeneous transformation matrices is first present. The model takes into account the runout and tilt errors of the spindle, the parts tolerances of the toolholder interfaces (spindle nose-toolholder and toolholder-cutting tool shank), as well as the cutting tool edge tolerance. The paper concludes with a simulation based on common values of the spindle elements. The proposed model is expected to provide insights into the advanced tolerance analysis of the spindle system. © IMechE 2005.